Developments in kidney xenotransplantation - Xu, Haiyan; He, Xiaozhou (Frontiers in Immunology, 2024)
The search for kidney xenografts that are appropriate for patients with end-stage renal disease has been ongoing since the beginning of the last century. The major cause of xenograft loss is hyperacute and acute rejection, and this has almost been overcome via scientific progress. The success of two pre-clinical trials of α1,3-galactosyltransferase gene-knockout porcine kidneys in brain-dead patients in 2021 triggered research enthusiasm for kidney xenotransplantation. This minireview summarizes key issues from an immunological perspective: the discovery of key xenoantigens, investigations into key co-stimulatory signal inhibition, gene-editing technology, and immune tolerance induction. Further developments in immunology, particularly immunometabolism, might help promote the longterm outcomes of kidney xenografts.